Framework Documentation With Patterns: An Empirical Study - Ho, Sin Ban (2008)
The objective of this thesis is to empirically investigate different documentation philosophies for effective transfer of knowledge in teaching new framework users, especially, when patterns style documentation was used as a means of knowledge organization, interaction and representation. A series of controlled experiments, which served as the case studies, were set up to compare the various documentation philosophies, namely traditional step by step, minimalist, patterns style, and extended javadoc (Jdoc) documentation.